2013 International Conference on Information Science and Applications (ICISA) 2013
DOI: 10.1109/icisa.2013.6579465
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation Problem in Android

Abstract: Due to the nature of an open operating system, Android framework cannot avoid the fragmentation problem. To address this, cost of time and efforts to devise application tests in mobile environment is unavoidable. In this paper, we propose two methods that handle android fragmentation problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The problem of mobile device fragmentation is well-known and is considered as one of the most difficult aspects of the mobile testing [9][10][11]. In particular, this paper addresses the problem of the selection of the optimal set of devices for testing as often discussed by the software engineering practitioners' community in numerous forums and blogs.…”
Section: B Using Combinatorial Methods To Provide Coverage Of the Dementioning
confidence: 99%
“…The problem of mobile device fragmentation is well-known and is considered as one of the most difficult aspects of the mobile testing [9][10][11]. In particular, this paper addresses the problem of the selection of the optimal set of devices for testing as often discussed by the software engineering practitioners' community in numerous forums and blogs.…”
Section: B Using Combinatorial Methods To Provide Coverage Of the Dementioning
confidence: 99%
“…Furthermore, it can also create security vulnerabilities, as older versions of Android may have a different levels of security than the latest version [251]. Several factors contribute to the fragmentation of Android versions, including the slow pace of updates from device manufacturers, many different Android devices on the market, and the fact that some devices are no longer supported by their manufacturers [252]. This can make it difficult for users and developers to ensure that their devices and apps are running the latest version of the Android.…”
Section: Version Fragmentationmentioning
confidence: 99%
“…According to our finding F8, there are more than 19,000 device models in our dataset. Such a fragmentation brings significant challenges to software engineering practices for mobile apps, such as app design, development, maintenance, quality assurance, and revenue generation [45], [46], [47], [48]. A recent study [49] (in 2013) showed that 94% of mobile-app developers who avoid the Android platform cite fragmentation as the main reason.…”
Section: Addressing Device-specific Featuresmentioning
confidence: 99%